Identification, content, and distribution of type VI collagen in bovine tendons - Carvalho, Hernandes F. (2006)
Tendon composition changes according to differentiation, mechanical load, and aging. In this study, we attempted to identify, localize, and quantify type VI collagen in bovine tendons. Type VI collagen was identified by the electrophoretic behavior of the alpha chains and Western blotting, and by rotary shadowing. Type VI collagen was extracted from powdered tendon with three sequential 24-h extractions with 4 M guanidine-HCl. The amount of type VI collagen was determined by enzyme-linked immunosorbent assay for purely tensional areas and for the compressive fibrocartilage regions of the deep flexor tendon of the digits, for the corresponding fetal and calf tendons, and for the extensor digital tendon. The distal fibrocartilaginous region of the adult tendon was richer in type VI collagen than the tensional area, reaching as much as 3.3 mg/g (0.33%) of the wet weight. Calf tendons showed an accumulation of type VI at the fibrocartilage site. Immunocytochemistry demonstrated that type VI collagen was evenly distributed in the tensional areas of tendons but was highly concentrated around the fibrochondrocytes in the fibrocartilages. The results demonstrate that tendons are variable with regard to the presence and distribution of type VI collagen. The early accumulation of type VI collagen in the region of calf tendon that will become fibrocartilage in the adult suggests that it is a good marker of fibrocartilage differentiation. Furthermore, the distribution of type VI collagen in tendon fibrocartilage indicates that it organizes the pericellular environment and may represent a survival factor for these cells. © Springer-Verlag 2006.